EXPERIMENTAL-BASED OPTIMIZATION MODELING OF COAL BLENDING USING PROXIMATE ANALYSIS TO MEET MT-47 POWER PLANT FUEL STANDARDS - Taufik Arief; Eddy Ibrahim; IE. Frasetyo; Maulana Yusuf (RADJA PUBLIKA, 2026)
This study aims to evaluate the feasibility of using blended coal as fuel for steam power plants (PLTU) by examining the quality of MT-47 coal from PT Bukit Asam through proximate analysis and statistical trend analysis. High-calorie coal (A) and low-calorie coal (B) were blended at ratios of 30:70, 40:60, 50:50, and 60:40, and then tested in the laboratory to determine the intrinsic moisture (IM), ash content, volatile matter (VM), and fixed carbon (FC) content. The test results showed that the IM value ranged from 24.78–27.93%, ash from 4.52–5.79%, VM from 36.05–39.21%, and FC from 30.22–31.50% (adb). Regarding the quality of MT-47, only the ash parameters at the 30:70 and 40:60 ratios meet the standard limits, while the IM, VM, and FC at all ratios do not comply with the MT-47 specifications. Linear regression analysis and Pearson correlation coefficients show a very strong linear relationship between the blending ratio and all proximate parameters, with high correlation values (|r| > 0.95) and coefficients of determination above 95%, thus indicating a consistent trend of quality changes due to variations in the blending ratio. Overall, the 30:70 ratio is the composition closest to the quality of MT-47, although this coal mixture still requires further quality improvement processes to be suitable for direct use as PLTU fuel.